Classroom perception in higher education: The impact of spatial factors on student satisfaction in lecture versus active learning classrooms - Jin, Shitao; Peng, Lei (Frontiers in Psychology, 2022)
Driven and influenced by learning theory and information technology, the form of the classroom environment in higher education is constantly changing. While traditional lecture classrooms focus on efficient learning modes and economical space layouts, active learning classrooms focus more on active learning psychology and adaptive space perception. Although existing studies have explored the development of educational and technological domains in the classroom, a comparative study of these two classroom environments and students’ learning perceptions has not been conducted. Hence, using a questionnaire, this study collected subjective perception reports from 316 students in traditional lecture classrooms versus active learning classrooms. By analyzing Likert scales of student satisfaction in two classroom environments, the study found the following: learning support dimensions in both classroom environments required improvements; space and furniture perception, physical and decorative environment are critical factors in improving students’ perceptions in the lecture classroom; space perception is the critical factor in enhancing students’ perception in the active learning classroom. These findings can serve as good references and useful insights for future classroom design and optimization to build enriched and inclusive learning environments to help students gain a more positive perception of learning.